Value Chain Map of Coffee Commodities in Central Aceh Regency in the Implementation of Inclusive Business Model - Fantashir Awwal Fuqara; Yulia Windi Tanjung (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This study aims to describe the Value Chain of coffee commodities in Central Aceh Regency and analyze the Value Chain Map of coffee commodities in Central Aceh Regency in the implementation of the Inclusive Business Model. This research was conducted in Central Aceh District, Aceh Province. This research was conducted in March–August 2023. The data used is in the form of primary data and secondary data. The sampling method with non-probability sampling uses the purposive sampling method. The data analysis method used is qualitative data analysis. Data analysis techniques use the Value Chain Map approach. The value chain of coffee in Central Aceh Regency the first distribution pattern is farmers selling directly to middlemen to exporters and consumers, the second pattern is farmers to middlemen to cooperatives and consumers, then the third pattern is farmers to middlemen to MSMEs Coffee Processors and consumers. The implementation of an inclusive business model for coffee commodities in Central Aceh Regency is through a partnership or collaboration between coffee farmers and the Baitul Qiradh Baburrayyan Cooperative. The highest value for farmers who are members of cooperatives is in principle 2 of effective market linkage (3.8). The lowest value is principle 3 fair and transparent governance (3.0). The highest value in non-cooperative farmers is principle 1 chain-wide collaboration (2.5). The lowest value is the 6 principles of Measurement of outcome (2.0). The inclusive business model is very profitable for farmers who join cooperatives because farmers get premiums, higher prices, infrastructure development, coaching and capital to improve farmer welfare.